Total Quality Control (TQC) Analysis in Identification of Damage to Coffee Production at PT XYZ - Nugraha, Isna; Pulansari, Farida; Ramadhan, Gilang (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
PT XYZ is a coffee processing company with a production process involving five stages: sorting, drying, peeling, selecting, and packaging coffee beans. This study applies the Total Quality Control (TQC) approach to identify factors causing product defects. Methods include p-control charts to monitor quality variations statistically and fishbone diagrams to analyze root causes. Data were collected through interviews, observations, and company documents. The analysis revealed seven data points exceeding the upper control limit (UCL) and 11 below the lower control limit (LCL). Human errors, inadequate training, and machine-related issues were identified as the primary causes of defects. Environmental factors, such as inconsistent humidity levels, were also found to affect product quality. The findings provide actionable insights for PT XYZ to implement Kaizen-based improvements, focusing on minimizing defects, enhancing production quality, and maintaining product consistency. These measures are expected to support the company in achieving better control over quality processes and ensuring the stability of its coffee product standards.